Characteristics of homocysteine-induced multidrug resistance of human MCF-7 breast cancer cells and human A2780 ovarian cancer cells - Lukyanova, N.Yu. (Experimental Oncology, 2010)
Aim:To study the influence of homocysteine on the mechanisms of drug resistance formation. Methods: In current study human MCF-7 breast cancer cells and A2780 ovarian cancer cells sensitive to anticancer drugs were used. To access the viability of cells, we applied 3-[4,5-dimethylthiazol-2–1]-2,5-diphenyltetrazolium bromide colorimetric assay (MTT-test). Expression of Bcl-2, p-glycoprotein (P-gp), glutathione S-transferase (GST) and E-cadherin was studied by immunocytochemistry. Results: A2780 and MCF-7 cells were treated by homocysteine. It was shown that every next treatment with homocysteine (up to 5th) decreased the sensitivity of A2780 and MCF-7 cells to cytotoxic drugs. Immunocytochemical study of molecular profile of A2780 and MCF-7 cells after long-term cultivation with homocysteine has been carried out and has revealed that such treatment resulted in the induction of Bcl-2, P-gp, GST and E-cadherin expression. This indicates that incubation of studied cells with homocysteine leads to simultaneous induction of expression of drug resistance markers to cisplatin and doxorubicin. Conclusion: Cultivation of MCF-7 and A2780 cells with homocysteine leads to simultaneous development of resistance to doxorubicine and cisplatin. The development of drug resistance is diverse for different drugs and varies among cell lines.